Thin Metal Foils Effect of Quench Temper and Annealing to The Mechanical Properties and Microstructure of Stainless Steel for Electronic and Biomedical Application: Quench Tempering and Annealing in Thin Metal Foils - Aziz, Abdul (LPPM ITK, 2024)
The change of mechanical properties and microstructure occur in austenitic stainless steel thin metal foil SUS 316. The occurence studied after quench tempering treatment at 900oC to the Stainless Steel thin metal foils and holded for 1 hour, 2 hour and 3 hours. The experiment subjected to the stainless steel thin metal foils with fine grains and coarse grains. Based on SEM-EBSD investigation, No. martenstic phase transformation (MPT) occur in the microstructure of SUS 316 thin metal foils. The change of microstructure indicated by the change of grain misorientation (GMO) in the grain of SUS 316 thin metal foils. The hardness increase according to the increasing the holding time. The increase of the hardness in SUS 316 thin metal foils have dependency with the surface roughening behavior in thin metal foils. The surface roughening has great effect to the formability of thin metal foils SUS 316. The other findings are the surface surface roughening decrease with the increase of the hardness of SUS 316 thin metal foils. In other words, the surface roughening decrease according to the increase of the holding times. Key Words : Microstructure; Grain Misorientation (GMO); Fine Grains, SEM-EBSD; Coarse Grains